Deubiquitylase USP25 prevents degradation of BCR-ABL protein and ensures proliferation of Ph-positive leukemia cells - Shibata, Norihito; Ohoka, Nobumichi; Tsuji, Genichiro; Demizu, Yosuke; Miyawaza, Keiji; Ui-Tei, Kumiko; Akiyama, Tetsu; Naito, Mikihiko (Oncogene, 2020)
Fusion genes resulting from chromosomal rearrangements are frequently found in a variety of cancer cells. Some of these are known to be driver oncogenes, such as BCR-ABL in chronic myelogenous leukemia (CML). The products of such fusion genes are abnormal proteins that are ordinarily degraded in cells by a mechanism known as protein quality control. This suggests that the degradation of BCR-ABL protein is suppressed in CML cells to ensure their proliferative activity. Here, we show that ubiquitin-specific protease 25 (USP25) suppresses the degradation of BCR-ABL protein in cells harboring Philadelphia chromosome (Ph). USP25 was found proximal to BCR-ABL protein in cells. Depletion of USP25 using shRNA-mediated gene silencing increased the ubiquitylated BCR-ABL, and reduced the level of BCR-ABL protein. Accordingly, BCR-ABL-mediated signaling and cell proliferation were suppressed in BCR-ABL-positive leukemia cells by the depletion of USP25. We further found that pharmacological inhibition of USP25 induced rapid degradation of BCR-ABL protein in Ph-positive leukemia cells, regardless of their sensitivity to tyrosine kinase inhibitors. These results indicate that USP25 is a novel target for inducing the degradation of oncogenic BCR-ABL protein in Ph-positive leukemia cells. This could be an effective approach to overcome resistance to kinase inhibitors.